Síntese e caracterização de pós nanométricos de óxidos de zinco e titânio pelo método sol-gel assistido por amido de mandioca (tapioca) - ALMEIDA, Willians Lopes de (2020)
This work investigated the obtaining nanomaterials of ZnO, TiO2 and three compositions varying the mass ratio between ZnO and TiO2 (1:3, 1:1 and 3:1), using a sol-gel method assisted by starch from cassava (tapioca). The materials were studied through X-Ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Transmission Electron Microscopy (MET), Diffuse Reflectance Spectroscopy in UV/Visible and Photoluminescence (PL). From the study of ZnO synthesis, it was possible to infer that zinc cations interact with starch C-O groups, according to FTIR results. The morphological and photophysical characterization showed that the synthesis method is prone to form nanoparticles (34 nm) of ZnO at low temperature (500ºC) with the lowest band gap (3.14 eV). Under these conditions, nano-ZnO showed the lowest rate of recombination between photogenerated charge carriers. About TiO2, it was found that tapioca does not participate effectively in the reaction to form titanium oxide nanoparticles, its role being limited to a possible impregnation on the surface of these nanoparticles. However, this impregnation was fundamental for the composition of phases, as shown by the results by XRD. The photophysical characterization of TiO2 showed that the band gap decreases as the anatase content decreases, just as it was found, through the PL spectrum, that TiO2 calcined at 600ºC maintained the lowest recombination rate between photogenerated charge carriers. Regarding the 1:3, 1:1 and 3:1 compositions, the analysis by XRD showed that the crystallite size for ZnO increased as the TiO2 content decreased in the composition. Evidence of a probable interstitial doping of titanium atoms in the ZnO network, especially in the 3:1 composition, was detected due to the increase in the lattice parameters. The lowest direct band gap (3.16 eV) was found for the 3:1 composition and the highest (3.28 eV) for 1:3. The PL results show that the 1:1 composition remained with the lowest rate of recombination between photogenerated charge carriers, while the 3:1 sample showed the highest. This effect was attributed to interstitial doping as the XRD results suggest. In general, it was possible to obtain nanostructures of ZnO, TiO2 and compositions between these oxides, by the synthesis method proposed in this work, using a biodegradable, renewable, low-cost and abundant natural polymer.